The use of collimator angle optimization and jaw tracking for VMAT‐based single‐isocenter multiple‐target stereotactic radiosurgery for up to six targets in the Varian Eclipse treatment planning system. Issue 9 (19th July 2021) - Pudsey, Lauren M. M.; Cutajar, Dean; Wallace, Alex; Saba, Anastasia; Schmidt, Laurel; Bece, Andrej; Clark, Catherine; Yamada, Yoshiya; Biasi, Giordano; Rosenfeld, Anatoly; Poder, Joel
Abstract: Purpose: Island blocking occurs in single‐isocenter multiple‐target (SIMT) stereotactic radiotherapy (SRS) whenever targets share multi‐leaf collimator (MLC) leaf pairs. This study investigated the effect on plan quality and delivery, of reducing island blocking through collimator angle optimization (CAO). In addition, the effect of jaw tracking in this context was also investigated. Methods: For CAO, an algorithm was created that selects the collimator angle resulting in the lowest level of island blocking, for each beam in any given plan. Then, four volume‐modulated arc therapy (VMAT) SIMT SRS plans each were generated for 10 retrospective patients: two CAO plans, with and without jaw tracking, and two plans with manually selected collimator angles, with and without jaw tracking. Plans were then assessed and compared using typical quality assurance procedures. Results: There were no substantial differences between plans with and without CAO. Jaw tracking produced statistically significant reduction in low‐dose level parameters; healthy brain V10% and mean dose were reduced by 9.66% and 15.58%, respectively. However, quantitative values (108 cc for V10% and 0.35 Gy for mean dose) were relatively small in relation to clinical relevance. Though there were no statistically significant changes in plan deliverability, there was a notable trend of plans with jaw tracking having lower gamma analysis pass rates. Conclusion: These findings suggest that CAO has limited benefit in VMAT SIMT SRS of 2–6 targets when using a low‐dose penalty to the healthy brain during plan optimization in Eclipse. As clinical benefits of jaw tracking were found to be minimal and plan deliverability was potentially reduced, a cautious approach would be to exclude jaw tracking in SIMT SRS plans.